2013
DOI: 10.1111/nmo.12068
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal accommodation induced by meal ingestion: differential responses to gastric and colonic volume loads

Abstract: Meal ingestion induces a metered and region-specific response of the abdominal walls to accommodate the volume load. Abnormal abdominal accommodation could be involved in postprandial bloating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 31 publications
(93 reference statements)
2
26
0
2
Order By: Relevance
“…Previous studies in healthy subjects using abdominal CT imaging combined with EMG of the abdominal walls showed that the anterior wall and the diaphragm, adapt their muscular tone to the intraabdominal content. Increases of intraabdominal content, induce an abdominal accommodation response, featuring a relaxation and upward displacement of the diaphragm with cephalad expansion of the abdominal cavity and limited impact on the anterior abdominal wall . The present study shows that abdominal distension after eating lettuce in our patients is produced by a paradoxical contraction of the diaphragm with caudo‐ventral redistribution of abdominal content.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies in healthy subjects using abdominal CT imaging combined with EMG of the abdominal walls showed that the anterior wall and the diaphragm, adapt their muscular tone to the intraabdominal content. Increases of intraabdominal content, induce an abdominal accommodation response, featuring a relaxation and upward displacement of the diaphragm with cephalad expansion of the abdominal cavity and limited impact on the anterior abdominal wall . The present study shows that abdominal distension after eating lettuce in our patients is produced by a paradoxical contraction of the diaphragm with caudo‐ventral redistribution of abdominal content.…”
Section: Discussionsupporting
confidence: 53%
“…The study was designed to maximize both the cognitive and metabolic responses to a meal. For this purpose we used a well‐characterized standard meal with controlled and varied nutrient composition . Participants were instructed to consume the meal to their own level of maximal satiation in order to induce a standard cognitive response.…”
Section: Discussionmentioning
confidence: 99%
“…The probe meal has been previously described . In brief, it was an aqueous mixture of nutrients (0.8 kcal/mL) containing per liter meal 833 mL of a nutrient preparation (Edanec; Abbott, Madrid, Spain) and 27 g non‐absorbable polyethylenglycol 4000.…”
Section: Methodsmentioning
confidence: 99%
“…These changes were observed also during more physiological conditions such as meal ingestion [92] . In supine position, these responses to volume load express a similar posture-dependent coordination: the diaphragm in this case contracts to exert anti-gravitational activity while the anterior abdominal wall remains inactive.…”
Section: Impaired Abdominal Emptingmentioning
confidence: 72%